Willow tree shoot module length and the attack and survival pattern of a shoot-galling sawfly, Euura atra (Hymenoptera: Tenthredinidae) - Price, Peter; Roininen, Heikki; Tahvanainen, Jorma (Entomologica Fennica, 1997)
A small population of the shoot-galling sawfly , Euura atra (Jurine), attacking the willow, Salix alba L. (Salicaceae) in Joensuu, Finland, showed strong preference-performance linkage between female ovipositional choices and survival of progeny. Although shoot lengths on trees were most common in the classes 200-400 mm, the probability of attack increased with shoot length until rare long shoots over 400 mm had a 50-80% probability of attack. The regression of attack probability on shoot length class accounted for 91% of the variance in attack. Attack was significantly greater on longer shoot length classes than that predicted by random attack based on total shoot length available per class, or total number of shoots per class. As shoot length increased the mean number of galls per shoot increased from 0 to 3 per shoot, and establishment and survival of progeny increased from 0 to over 60%. Shoot length class accounted for 70% and 50% of the variance in larval establishment and ultimate survival respectively, while attack by carnivores showed no pattern and had no explanatory power. The results are consistent with those from studies on seven other Euura species showing attack on rapidly growing plants, an ovipositional preference for longer shoots, higher survival on longer shoots, and no detectable effects of carnivores on pattern generation. The study aids in the development of a strong comparative ecology of galling sawflies and the eventual development of empirically based factual theory on their population dynamics.